PENANGANAN KONFLIK DI REPUBLIK AFRIKA TENGAH OLEH PBB PADA TAHUN 2013 - Rizky Ananda P.B.S Ananda P.B.S; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The conflict occurred in the countries of Africa difficult hard for found Solutions Towards shown to a peace . some countries in Africa Condensed between the Conflict That lie Rwanda , Congo , Nigeria , Sudan , Kenya , Somalia and ALSO that already provide victim pathetic. Here the author Trying to write research related to knowing about background occurrence of conflict in the Central African Republic , and also to study the response of the Islamic World about this issues. For analyze research , author make question is: why UN Security Council Participate handle sectarian conflict in the Central African Republic . The research method used is qualitative research . can qualitative research is defined as a series of activities or processes to capture information from the condition naturally an object , associated with the settlement of a problem connected with objek The resolution problem , Viewed From a theoretical and practical view . Introduction to use grouping State Level Analysis , theory of her is an international organization as well as liver and Conflict Resolution international and analyze some reason why type And Conflict in Central African Republic UN Peacekeeping involved in sending peacekeepers are MISCA forces and impose penalties against some countries members who do not obey the CharterKeyword: Konflik, MISCA, Dewan Keamanan PBB